2017
DOI: 10.1007/s00705-017-3385-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete cryspovirus genome sequences from Cryptosporidium parvum isolate Iowa

Abstract: Bisegmented dsRNA viruses that infect most or all isolates of apicomplexan parasite Cryptosporidium parvum are currently assigned to a single species, Cryptosporidium parvum virus 1, in genus Cryspovirus, family Partitiviridae. An analysis of existing sequence data suggested that the complete sequences of both cryspovirus genome segments, dsRNA1 and dsRNA2, had yet to be determined. We therefore set out to accomplish this for the virus strain that infects C. parvum isolate Iowa. The results suggest that severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Cryptosporidium parvum virus 1 (CSpV1), a member of the family Partitiviridae, genus Cryspovirus, is a double-stranded RNA (dsRNA) virus of C. parvum and many other Cryptosporidium spp 20 . CSpV1 virus is non-enveloped with a genome comprised of two distinct dsRNAs, designated as CSpV1-dsRdRp (1836 bp) and CSpV1-dsCA (1510 bp) 21 . CSpV1-dsRNAs are not 5'-capped and unlikely to be 3'polyadenylylated 20,22 .…”
mentioning
confidence: 99%
“…Cryptosporidium parvum virus 1 (CSpV1), a member of the family Partitiviridae, genus Cryspovirus, is a double-stranded RNA (dsRNA) virus of C. parvum and many other Cryptosporidium spp 20 . CSpV1 virus is non-enveloped with a genome comprised of two distinct dsRNAs, designated as CSpV1-dsRdRp (1836 bp) and CSpV1-dsCA (1510 bp) 21 . CSpV1-dsRNAs are not 5'-capped and unlikely to be 3'polyadenylylated 20,22 .…”
mentioning
confidence: 99%
“…In order to address the taxonomic classification of this mycovirus, we aligned the full-length protein sequences of the RdRp and the hypothetical protein with those reported for representative members of the genera Alphapartitivirus, Betapartitivirus, Deltapartitivirus, Cryspovirus, and Gammapartitivirus [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The resulting maximum likelihood (ML) phylogenetic tree, which was generated with both proteins by using the best-fit model of LG + G (with 1000 bootstrap replicates), further suggested that the mycovirus identified in strain T673 of T. harzianum belongs to the Partitiviridae family ( Figure 2 ) and supports the results of the BLASTp searches.…”
Section: Resultsmentioning
confidence: 99%
“…The 5′-non-translated regions (NTRs) of dsRNA1 are of the same length and remain intact ( 8 , 67 ), however, the 3′-NTRs of dsRNA1 and the NTRs of dsRNA2 show amino acid truncations ( 71 ). Notably, multiple shared conserved positive strand sequences are observed in the dsRNA1 and dsRNA2 of the isolated CSpV1-Iowa strain ( 72 ). These regions are also fully or partially conserved in other isolates.…”
Section: Parasitic Protozoan: Structure and Life Cyclesmentioning
confidence: 99%